2021
DOI: 10.3390/jmmp5040127
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Adjustment of Welding Depth during Laser Micro Welding of Copper Using Superpositioned Spatial and Temporal Power Modulation

Abstract: For joining metallic materials for battery applications such as copper and stainless steel, laser beam micro welding with beam sources in the near-infrared range has become established in recent years. In laser beam micro welding, spatial power modulation describes the superposition of the linear feed motion with an oscillating motion. This modulation method serves to widen the cross-section of the weld seam as well as to increase the process stability. Temporal power modulation refers to the controlled modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The difference to T Process results from T OffsetStart = 30 ms and T OffsetEnd = 35 ms. Due to the complex course of the data for the processes with spatial power modulation, the presented range is limited to the time interval between 110 ms and 190 ms. Here, a verification is made whether the use of the iterative learning control makes it possible to compensate for effect of the non-uniformity of the weld penetration depth when using spatial power modulation [13].…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The difference to T Process results from T OffsetStart = 30 ms and T OffsetEnd = 35 ms. Due to the complex course of the data for the processes with spatial power modulation, the presented range is limited to the time interval between 110 ms and 190 ms. Here, a verification is made whether the use of the iterative learning control makes it possible to compensate for effect of the non-uniformity of the weld penetration depth when using spatial power modulation [13].…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…Good quality joints without any crack formation were observed due to low-stress generation during laser beam welding. Hummel et al [26] used spatial and temporal power modulation to control the weld penetration in laser beam welding of copper. They concluded that the position of minimum and maximum laser power is critical for the adjustment of weld seam geometry.…”
Section: Introductionmentioning
confidence: 99%